Development of emotion recognition in popular music and vocal bursts. Issue 5 (3rd July 2020) - Vidas, Dianna; Calligeros, Renee; Nelson, Nicole L.; Dingle, Genevieve A.
ABSTRACT: Previous research on the development of emotion recognition in music has focused on classical, rather than popular music. Such research does not consider the impact of lyrics on judgements of emotion in music, impact that may differ throughout development. We had 172 children, adolescents, and adults (7- to 20-year-olds) judge emotions in popular music. In song excerpts, the melody of the music and the lyrics had either congruent valence (e.g. happy lyrics and melody), or incongruent valence (e.g. scared lyrics, happy melody). We also examined participants' judgements of vocal bursts, and whether emotion identification was linked to emotion lexicon. Recognition of emotions in congruent music increased with age. For incongruent music, age was positively associated with judging the emotion in music by the melody. For incongruent music with happy or sad lyrics, younger participants were more likely to answer with the emotion of the lyrics. For scared incongruent music, older adolescents were more likely to answer with the lyrics than older and younger participants. Age groups did not differ on their emotion lexicons, nor recognition of emotion in vocal bursts. Whether children use lyrics or melody to determine the emotion of popular music may depend on the emotion conveyed.